Promoting Sustainable Development in Nigeria Through Rural Women’s Participation in Decision-Making About Renewable Energy Law and Policy - Ijoma, Uchenna (Université d'Ottawa / University of Ottawa, 2021)
“[T]o devise development planning without the participation of [rural] women is like using four fingers when you have ten.” Both lack of access to energy and climate change threatens poverty reduction and sustainable development in Nigeria. Most poor communities in Africa use inadequate fuels and are highly vulnerable to the impacts of climate change, with women bearing most of the social, economic, and environmental costs. Promoting access to affordable and sustainable energy through policy interventions is one crucial path to achieving sustainable development. Renewable energy offers countries the opportunity to meet the energy demands of the poorest and most vulnerable in each society, and thereby achieve many of the sustainable development goals, such as: hunger and poverty eradication, gender equity, affordable and clean energy, climate action, and maternal health. The Nigerian government is constantly formulating legal frameworks for renewable energy to expand the availability of energy (including electricity) to rural areas while reducing the impacts of climate change. Yet the extent to which these legal frameworks will be implemented successfully remain in doubt; as to date, Nigeria has been unable to achieve its stated goal of sustainable development. Why are renewable energy policies and laws in Nigeria not succeeding? This thesis asks whether one reason may be that Nigerian women living in rural areas have little role in both designing renewable energy laws and policies and participating in their effective implementation. This is a problem given that rural women are the primary users of unsustainable energy, they suffer most from its negative impacts, they are the main beneficiaries of rural electrification, and the closest to the needs and capacities of the population in rural communities. This thesis is mainly qualitative. Multiple approaches (feminist historical research, documentary or doctrinal analysis as well as analysis by specific illustrative examples) were used to explore the phenomenon of why the Nigerian government’s concerted efforts at developing the legal frameworks for renewable energy have not yielded their desired goals of promoting sustainable development, and what lessons could be learned from South Africa. In addition to contributing to the gender and renewable energy literature, the research attempts to develop a blueprint for inclusive approaches to renewable energy law. It investigates how renewable energy legal and institutional frameworks could effectively include rural women. Using ideas from feminist legal theorists, the thesis makes a case for why rural women should be considered suitable stakeholder participants. It concludes that renewable energy policy- and law-making processes which consider the voices and active participation of rural women could encourage an increase in the generation, distribution, and use of renewable energy in the poorest inaccessible areas while closing the gap between renewable energy policies and laws, and sustainable development. Finally, it recommends that renewable energy policies and laws should increase rural women’s participation by using among other things “recognition politics,” which allows for the representation of subordinate social groups in bodies such as Parliaments; for example, by using measures such as mandatory affirmative action – quota system clauses, and techniques such as“Taking Parliament to the People.”
Keywords: Renewable Energy; Lawmaking; Policymaking; Sustainable Development; Decision-making; Women; Participation; Nigeria; South Africa; Gender